1991
DOI: 10.1007/bf01800601
|View full text |Cite
|
Sign up to set email alerts
|

d‐Glyceric acidaemia: clinical report and biochemical studies in a patient

Abstract: D-Glyceric acidaemia is a very rare inherited metabolic disorder and clinical and biochemical presentations are quite heterogeneous. Regarding the clinical features, the patients can be divided into three groups: severe encephalopathy, sometimes with hyperglycinaemia; moderate clinical symptoms (i.e. moderate mental retardation or speech delay), metabolic acidosis and microcephaly; or the absence of clinical problems. Biochemical investigations performed in these patients have suggested disturbed fructose or/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…While liver activities of D-glycerate dehydrogenase and triokinase were normal, van Schaftingen [1989] demonstrated deficiency of hepatic D-glycerate kinase in a patient with D-glyceric aciduria described by Fontaine et al [1989] and Largillière et al [1991]. However, confirmation of that finding in other individuals with D-glyceric aciduria was never reported.…”
Section: Introductionmentioning
confidence: 56%
“…While liver activities of D-glycerate dehydrogenase and triokinase were normal, van Schaftingen [1989] demonstrated deficiency of hepatic D-glycerate kinase in a patient with D-glyceric aciduria described by Fontaine et al [1989] and Largillière et al [1991]. However, confirmation of that finding in other individuals with D-glyceric aciduria was never reported.…”
Section: Introductionmentioning
confidence: 56%
“…Fructose and serine loading tests resulted in a deficiency of Dglycerate kinase, indicating the potentially benign nature of the disease. Largillire et al [9] described a 3 year-old Turkish girl with profound encephalopathy, spastic tetraplegia and hypotrophy in whom a therapeutic trial with sodium benzoate decreased plasma D-glycerate without any clinical improvement and concluded that D-glyceric aciduria can only be a biochemical finding without any causal relationship with the various pathological symptoms associated with it.…”
Section: Discussionmentioning
confidence: 99%